Biodecoloración de tintes sintéticos industriales por bacterias termófilas con actividad enzima tipo lacasa - Salazar Torreblanca, Fiorela Virginia (2017)
In this work, the discoloration capacity of the thermophilic bacteria of the Cepario of the Enzymatic Biotechnology Laboratory was investigated with laccase type activities about industrial synthetic dyes, especially printing inks that are released in the industrial effluents at the time of the de-inking of the recycled paper. For this reason, thermophilic bacterial cultures Geobacillus thermoleovorans CB-13, Geobacillus thermoparaffinivorans CB-25, Geobacillus thermoleovorans FT-06 and Geobacillus kaustophilus TM-12 were selected, which showed higher laccase-like enzymatic activity in solid medium for the four substrates evaluated (2-MP; 2,6-DMP; ABTS and SRG). Geobacillus kaustophilus TM-12 was selected as having the highest potential for decolorization of synthetic dyes in tube discoloration tests. In the study of the removal kinetics of the biological treatment with Geobacillus kaustophilus TM-12, a percentage of discoloration higher than 75% was reached for azo dyes in periods of time less than 24 hours and changes were observed in the absorption spectra, indicating the chemical degradation of the dye. Likewise, the treatment of the simulated deinking effluent resulted in 60% discoloration at 14 hours evidencing the biodecoloring action of synthetic dyes during the biological treatment with thermophilic b